Selector-induced dynamic deracemization of a selectand-modified tropos BIPHEPO-ligand: application in the organocatalyzed asymmetric double-aldol-reaction - Maier, Frank; Trapp, Oliver (Angewandte Chemie. International edition, 2014)
Stereolabile interconverting catalysts open up the possibility of directing enantioselectivity in asymmetric synthesis by formation of diastereomeric complexes with chiral auxiliaries and deracemization. However, the stoichiometrically used auxilliaries can significantly limit the potential applications of such systems. We synthesized a new BIPHEPO tropos ligand containing achiral selectands in the backbone, which forms transient diastereomeric associates with amylose-tris-3,5-dimethylphenyl carbamate as a selector and thus deracemizes. The enantiomerically enriched BIPHEPO obtained was successfully used in the organocatalytic asymmetric double aldol addition of substituted methyl ketones to form benzaldehyde. This strategy combines an on-column deracemization with the high stereoinduction of chiral biarylphosphineoxides and opens up new possibilities in the field of self-amplified asymmetric syntheses.